Study protocol for a randomised controlled trial on the effect of local analgesia for pain relief after minimal invasive sacroiliac joint fusion: the ARTEMIS study. Issue 12 (20th December 2021) - Hermans, Sem M M; Nellensteijn, Jorm M; van Santbrink, Henk; Knoef, Rob; Reinders, Mattheus K; Hoofwijk, Daisy M N; Potters, Jan W; Movig, Kris L L; Curfs, Inez; van Hemert, Wouter L W
Abstract : Introduction: Chronic lower back pain is a common report in the general population. A dysfunctional sacroiliac joint (SIJ) is estimated to be responsible for one in five patients with lower back pain. Minimally invasive sacroiliac joint fusion (MISJF) is a surgical procedure to treat SIJ dysfunction. During the procedure, the SIJ is stabilised by implants inserted percutaneously under fluoroscopy guidance. Postoperatively, patients often report a lot of pain, which contributes to patients taking high doses of painkillers (opioids for example, ) and preventing early mobilisation. In several orthopaedic procedures, intraoperative infiltration of the wound bed results in decreased consumption of analgesics, earlier mobilisation and shorter hospitalisation time. The aim of this study is to investigate the effectiveness of intraoperative SIJ infiltration with analgesia in reducing postoperative pain after MISJF. Methods and analysis: We will perform a two-centre, prospective, double-blind, randomised controlled trial to determine whether SIJ infiltration with 1.5–5 cc bupivacaine 0.50% is superior to 1.5–5 cc placebo (NaCl 0.9%) in reducing postoperative pain in patients after MISJF, and to determine whether bupivacaine significantly reduces opioid use in the direct postoperative period. Patients will be randomised with 1:1 allocation for either bupivacaine (intervention) or placebo SIJ infiltration. Postoperative pain will be measured by the Visual Analogue Scale pain score at entry and exit recovery, 2, 4, 6, 24 and 48 hours postoperatively. Ethics and dissemination: This is the first trial that investigates the effectiveness of intraoperative SIJ infiltration with bupivacaine 0.50% in reducing postoperative pain after MISJF. If intraoperative SIJ infiltration with bupivacaine 0.50% proves to be effective, this might have important clinical implications, such as postoperative analgesics (opioids for example, ) consumption, earlier mobilisation and potentially shorter hospitalisation time. Trial registration number: NL9151.